Legal nature of the international tourist law (Journal of actual problems of jurisprudence, 2018)
The rapid development of international tourism and tourist activity creates States the needs of solving some problems of legal regulation. Approaches to solving the problems in this area, as well as in the field of international tourist activity reflects the obligations of States in international treaties and agreements. Features of international agreements are that from a legal point of view, they are binding on the parties. The shape of an international treaty in the legal regulation of tourist activity in Azerbaijan is developing in several directions. It may be noted as a form of international treaty of universal and regional nature , bilateral agreements concluded by Azerbaijan with a number of foreign countries in the sphere of legal regulation of tourist activities as well as institutional cooperation, undertaken by the Republic of Azerbaijan within the framework of various international organizations in the field of legal regulation of tourism activities. First of all should be noted the international universal treaty of legal regulation of tourist activity. It should also be noted that these types of contracts, currently installed in accordance with international tourism, aimed at regulating the relations are not so wide in its scope. Key words: Azerbaijan, tourism, tourist activity, universal treaty, form of universal treaty, the legal regulation.